What does current science tell us about the accuracy, reliability, and completeness of intoxicated witnesses? A case example of the murder of a prime minister - Hildebrand Karlén, Malin; de Bejczy, Andrea; Anckarsäter, Henrik; Guðjónsson, Gísli (Frontiers in Psychology, 2022)
Generally, the testimony of intoxicated witnesses has been considered relatively unreliable, but recent research has nuanced the knowledge base regarding these vulnerable witnesses. Purpose: To demonstrate the application of recent research findings regarding intoxicated witnesses to the statements made by a key witness to the murder of Olof Palme, Sweden’s prime minister, in 1986. An additional purpose was to illustrate the use of a nuanced calculation of blood alcohol concentration (BAC) for researchers. Method: The Palme murder has been debated since the crime was committed and no one has yet been sentenced. One of the witnesses was intoxicated and to estimate a range for his BAC at the time, a comprehensive BAC-calculation was conducted in this study to illustrate important factors to consider in these types of cases. Results: Through demonstration of the use of a nuanced BAC-formula and by applying recent research results from studies on intoxicated witnesses, it was estimated that the possible BAC of the witness in the Palme-case at the time of the witnessed crime ranged between BAC = 0 to BAC = 0.13, depending on type of alcoholic beverage consumed and whether the witness was a social or heavy drinker. This puts the witness either well within the span of maintained completeness as well as maintained accuracy-rate (if considering: lowest dose and heavy drinker), or slightly exceeding this span into the BAC-range of reduced completeness but maintained accuracy rate (if considering: highest dose and social drinker). He was questioned immediately, and thereafter repeatedly, and he reported similar information throughout the interviews, which is in line with previous results on information maintenance over repeated interviews among intoxicated witnesses. Conclusions: The current case example show how recent research on intoxicated witnesses can be applied in praxis, illustrating important factors for legal practitioners to consider when interpreting information from intoxicated witnesses. It also provides legal practitioners and researchers with an example of a structured approach to more nuanced BAC-calculations.